2021
DOI: 10.1029/2021gl093833
|View full text |Cite
|
Sign up to set email alerts
|

Decomposing Effective Radiative Forcing Due to Aerosol Cloud Interactions by Global Cloud Regimes

Abstract: The radiative forcing (RF) produced by aerosol remains a large source of uncertainty in climate models (IPCC, 2013). General Circulation Models (GCMs) show a wide range in their predictions of aerosol forcing, through the uncertainty in effective radiative forcing, due to aerosol-cloud interactions ( et al., 2020).Aerosol-cloud interactions are driven by a number of different effects, occurring on different timescales. Instantaneous effects will drive changes in the instantaneous radiative forcing due to aeros… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…This increase in the percentage of cloud dimming due to thin clouds with a decrease in f c may be attributed to the high amounts and extent of variation in f thin , which are minimum for Sc‐dominated overcast cloud regime and increases coherently with scene heterogeneity as f c decreases in the Cu‐dominated regime. Such a wide range of possible variations in CRE SW,TOA , even at fixed cloud cover, highlights the dominant role of thin clouds in controlling the SW radiative effect (Goren et al., 2023; McCoy et al., 2017, 2023).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This increase in the percentage of cloud dimming due to thin clouds with a decrease in f c may be attributed to the high amounts and extent of variation in f thin , which are minimum for Sc‐dominated overcast cloud regime and increases coherently with scene heterogeneity as f c decreases in the Cu‐dominated regime. Such a wide range of possible variations in CRE SW,TOA , even at fixed cloud cover, highlights the dominant role of thin clouds in controlling the SW radiative effect (Goren et al., 2023; McCoy et al., 2017, 2023).…”
Section: Resultsmentioning
confidence: 99%
“…A possible explanation of the non‐linear relationship between scriptL $\mathcal{L}$ and f thin for f c < 0.8 relies on the results of Goren et al. (2023), who demonstrated that the deeper the cloud cores, the thinner their anvils. These observations also aligns with our results of increase in cloud heterogeneity with f thin (as discussed previously in Section 3.2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Calculating the ERF aci then requires not only an analysis of how the regimes have changed but an analysis of the change in the occurrence of the regime (and potentially the combination of these two effects). This complicates the calcula tion of the ERF aci using present-day data and requires a GCM to estimate changes in regime frequency (Langton et al, 2021).…”
Section: Produce No Change In Occurrence As Aerosols Are Changedmentioning
confidence: 99%